Eosinophilic Granuloma Involving the Femoral Neck - Hoari Krishnan; Taek Rim Yoon; Kyung Soon Park; Je Hyoung Yeo (Case Reports in Orthopedics)
We present a very rare case of eosinophilic granuloma involving the neck of femur in a 17-year-old male. The patient was treated with curettage and autologous iliac crest bone grafting with prophylactic screw fixation, and the diagnosis was confirmed by histopathological examination. Currently, it has been 14 years since the first surgery and the patient is well with no recurrence or relapse, and the osteolytic lesion has disappeared.